CHINESE GRAMMAR AUTO-CORRECT WEBSITE CHINESEGRAMMARCHECKER.COM DEVELOPMENT MODEL - Julita Wangi; Kelly Rosalin; Theresia Theresia (Bina Nusantara University, 2019)
In the process of learning and using Chinese, Indonesia students may have grammatical errors due to negative migration of their native language. At present, there is no Mandarin grammar correction website or application that can answer the needs of Mandarin learners. Therefore, researchers want to try to provide a website chinesegrammarchecker.com that can answer the needs of Chinese language learners in Indonesia so as to facilitate Chinese language learners in mastering Chinese grammar. Hope researchers are learners can learn independently in making sentences in Chinese using proper and correct Chinese grammar. The method used in this study is a qualitative approach. The researcher will collect basic level Chinese grammar patterns in the textbooks used in the Chinese Language I courses, namely Er Ya Basic Chinese: Comprehensive Course (I) and Basic Chinese: Comprehensive Course (II). Then from these patterns user can check their sentences on this website. After the website chinesegrammarchecker.com was completed, then it was tested for several users to see the advantages and disadvantages of this website chinesegrammarchecker.com.